2022
DOI: 10.1177/24730114221125455
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Review: The Foot and Ankle in Long-Distance Running

Abstract: Distance runners represent a unique patient population. The cyclic activity associated with distance running leads to a high incidence of injury. Gait patterns, the extrinsic and intrinsic muscles of the foot and ankle, foot strike pattern, shoe wear considerations, alignment, and orthotics are also all important considerations that must be considered by the treating provider. The purpose of this work is to review relevant functional anatomy, recent studies on gait patterns in running, orthotics, and theory on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 118 publications
(166 reference statements)
0
6
0
Order By: Relevance
“…In addition, a study have shown that the FHL tendon is more likely to be damaged by running posture with a forefoot landing and running age [2]. When the overflexion of the ankle plantar reaches a certain load, athletes experience discomfort during the push-off phase of the gait cycle, while the athlete may report discomfort in the first metatarsophalangeal joint when the FHL is injured and in a subclinical state [14]. Because there are no obvious symptoms of FHL injury, athletes may make minor adjustments in the landing mode of the plantar region involved in FHL tendon when they feel unwell, in order to compensate for the pressure load in the area where the FHL tendon acts during running.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study have shown that the FHL tendon is more likely to be damaged by running posture with a forefoot landing and running age [2]. When the overflexion of the ankle plantar reaches a certain load, athletes experience discomfort during the push-off phase of the gait cycle, while the athlete may report discomfort in the first metatarsophalangeal joint when the FHL is injured and in a subclinical state [14]. Because there are no obvious symptoms of FHL injury, athletes may make minor adjustments in the landing mode of the plantar region involved in FHL tendon when they feel unwell, in order to compensate for the pressure load in the area where the FHL tendon acts during running.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ballet dancers, cases of FHL injuries are more commonly reported in long distance runners [5][6][7][8][10][11][12][13]. The injury may be caused by excessive plantarflexion of the ankle joint due to repetitive push-off maneuvers during prolonged running [2,7,10,14], which is inevitable in marathon training. Therefore, early diagnosis of FHL injuries in amateur marathon runners is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Running is a sport practised worldwide and seen as a healthy sport and is considered a highly physically demanding activity that requires great resistance from the structures that maintain the morphology of the foot [1][2][3][4][5][6][7][8]. Foot hyperpronation is defined as an excessive tendency to a foot posture index, which is related to the appearance of injuries in the foot and other levels of the musculoskeletal levels (fasciitis, ankle sprains, knee, or low back pain, for example) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle fatigue can be correlated with excessive foot pronation. The collapse of the foot structures will induce a change in their morphology, tending to excessive foot pronation or hyperpronation that may be induced by muscle fatigue after a period of running activity, as has been evaluated in several previous researches [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation